The Phytochemical Potential for Brain Disease Therapy and the Possible Nanodelivery Solutions for Brain Access - Liu, Yang; Chen, Zhouchun; Li, Aijie; Liu, Runhan; Yang, Haoying; Xia, Xue (Frontiers in Oncology, 2022)
Plant-derived phytochemicals have been gifted human with vast therapeutic potentials. Yet, the unique features of the blood-brain barrier significantly limited their accession to the target tissue and thusly clinical translation in brain disease treatment. Herein, we explore the medicinal outcomes of both the rare examples of phytochemicals that can easily translocate across the blood-brain barrier, as well as most of the phytochemicals that were reported with brain therapeutic effects but bizarre amount of dosage is required due to their chemical nature. Lastly, we offer the nanodelivery platform that is capable of optimizing the targeted delivery and application of the none-permeable phytochemicals as well as utilizing the permeable phytochemicals for boosting novel applications of nanodelivery toward brain therapies.